Pengaruh E-Modul Berbasis Problem Based Learning dan Pendekatan STEM terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Muhammad Farkhan Tamam; Iswahyudi Joko Suprayitno; Eko Andy Purnomo (Mandalika Mathematics and Educations Journal, 2025)
Students' low problem-solving ability remains a problem in education. This study examines the effect of using PBL and STEM-based e-modules on mathematical problem-solving abilities in elementary to high school students focused on mathematics. The aim is to determine whether the e-modules used affect students' mathematical problem-solving abilities. The method used in this study is a system literature review (SLR) by reviewing articles from Google Scholar and Knowledge Maps sources from 2020 to 2025. The review process includes three stages: planning, implementation, and reporting. The results show that E-modules that integrate the PBL model, the STEM approach, or a combination of both are effective in improving students' ability to solve mathematical problems. These findings indicate that an innovative, student-centered learning model facilitated by e-modules is a potential strategy to address the challenges of problem-solving abilities in mathematics education.